Exosome-Based Liquid Biopsy in Early Screening and Diagnosis of Cancers - Xuying Hao; Zihan Liu; Feifei Ma; Tuo Li; Chengbin Liu; Ning Wang; Jiebing Guan; Ningning He; Jiao Liu; Shujuan Lu; Huijuan Song; Jianguo Li; et al. (Dose-Response)
Background: Liquid biopsy, analyzing the expression and variation of circulating tumor cell (CTC) or circulating tumor nucleic acid genes in peripheral blood, can obtain the information of tumorigenesis, metastasis and treatment, which has a potentially broader and complementary applications in the precision cancer medicine. Small vesicles, like exosomes which belongs to extracellular vesicles (EVs), which released by living cells into the vicinal surrounding biofluids, especially cells from carcinoma. Tumor-derived materials were contained by exosomes, totally including proteins, nucleic acid genes, and lipid, etcetera for instance metabolites. Besides, molecules which were synchronously belongings and carried on exosomal surface can tolerable provides crucial clues regarding their origin. Thus, classified the types of vesicles and enrich features from tissue-specific sources become presumably achieved. Therefore, exosomes and other EVs have emerged as a liquid biopsy platform for early screening and diagnosis of cancers, which constantaneously carry-over multitudinous surface molecules also throw clues regarding their origin. It is feasible to sort vesicles types, intake with approach channel to enrich the characteristics from tissue-specific origin. Based on the property that exosomes are remarkably stable in body fluids, which can amenity gathered in plasma or urine, it can be used for meticulous clinical evaluation particularly in the early stages of carcinoma. Therefore, exosomes have aroused immense interest in the study of biomarkers. Conclusions and Perspectives: This review aims to summarize the potential exosomal biomarkers especially exosomal miRNAs for exosome-based liquid biopsy in early screening and diagnostic of cancers, including lung cancer, breast cancer (BC), kidney cancer, prostate cancer (PCa), colorectal cancer (CRC), and summarizes the traditional and novel technologies for isolating exosomes and for detecting exosomal-based biomarkers, including exosomal proteins and exosomal nucleic acids. Finally, the limitations and prospects of exosome-based liquid biopsy in the early screening and diagnosis of cancers were discussed briefly.